2017
DOI: 10.1016/j.jclepro.2017.06.104
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of alumina-graphene hybrid nano-cutting fluid in hard turning

Abstract: Nanofluid (NF) is a colloidal mixture of metallic or non-metallic particles of nanometre-size in a base fluid. In the present investigation, a hybrid nano-cutting fluid with better thermal and tribological properties has been developed by mixing alumina based nanofluid with graphene nanoplatelets (GnP) in the volumetric concentrations of 0.25, 0.75 and 1.25 vol. %. The prepared hybrid and alumina mixed nanofluids are characterized for their thermal conductivity, viscosity, specific heat and density in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(55 citation statements)
references
References 47 publications
(15 reference statements)
1
47
0
1
Order By: Relevance
“…The friction is reduced by the nano-ball bearing phenomenon of the employed NF between the sliding surfaces. Along with this, the enhanced wetting surface can facilitate improved heat removal [33]. As such, the graphite NF has the lowest viscosity and the highest thermal conductivity ( Table 2).…”
Section: Effect Of Cutting Parameter and Nano-fluid Condition For Thementioning
confidence: 99%
“…The friction is reduced by the nano-ball bearing phenomenon of the employed NF between the sliding surfaces. Along with this, the enhanced wetting surface can facilitate improved heat removal [33]. As such, the graphite NF has the lowest viscosity and the highest thermal conductivity ( Table 2).…”
Section: Effect Of Cutting Parameter and Nano-fluid Condition For Thementioning
confidence: 99%
“…The authors also suggested focusing on the further studies of the application of MQL with hybrid nanofluids. Singh, R.K. et al [30] evaluated the performance of alumina-graphene hybrid nanofluid in hard turning. The experimental results revealed that the addition of graphene in alumina nanofluid enhanced the performance of hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that blending of graphite nanoparticles with base fluid enhances its tribological properties because of the lower friction coefficient [15], while MoS 2 and graphite solid lubricants reduce the surface roughness and the cutting force during machining [16]. Researchers also observed improved surface quality and reduction of the tool wear, cutting force, and chip thickness compared to dry and conventional wet machining [17,18]. Additionally, Amrita et al [19] showed that MQL method reduced the surface roughness, cutting force, cutting temperature and tool wear by 30%, 54%, 25% and 71%, respectively in comparison to conventional wet machining.…”
Section: Introductionmentioning
confidence: 99%